Martian electron foreshock from MAVEN observations. Issue 2 (2nd February 2017) - Meziane, K.; Mazelle, C. X.; Romanelli, N.; Mitchell, D. L.; Espley, J. R.; Connerney, J. E. P.; Hamza, A. M.; Halekas, J.; McFadden, J. P.; Jakosky, B. M.
Abstract: Flux enhancements of energetic electrons are always observed when the Mars Atmosphere and Volatile EvolutioN (MAVEN) spacecraft is magnetically connected to the shock. The observations indicate that the foreshock electrons consist of two populations. The most energetic ( E ≥237 eV) originate from a narrow region at the nearly perpendicular shock. They always appear as spikes, and their flux level reaches a maximum when the angle θ B n approaches 90°. The other population emanates from the entire Martian bow shock surface, and the flux level decreases slightly from the quasi‐parallel to quasi‐perpendicular regions. A detailed examination of the pitch angle distribution shows that the enhanced fluxes are associated with electrons moving sunward. Annulus centered along the interplanetary magnetic field direction is the most stringent feature of the 3‐D angular distribution. The gyrotropic character is observed over the whole range of shock geometry. Although such signatures in the electron pitch angle distribution function strongly suggest that the reflection off the shock of a fraction of the solar wind electrons is the main mechanism for the production of Martian foreshock electrons, the decay of the flux of the second population on the other hand has yet to be understood. Key Points: Two types of energetic electron populations are present upstream of the Martian bow shock Energetic electrons emanate from the entire bow shock surface of Mars Similar and distinct features between the terrestrial and Martian foreshocks are identified